PERANCANGAN RANGKAIAN BOOTSTRAP DENGAN IC IR2110 DAN SISTEM INVERTER SATU FASA TOPOLOGI H-BRIDGE BERBASIS IGBT IRG4PC50WD - Maksum Agung Praptomo; Iwan Setiawan; Denis Denis (Transient: Jurnal Ilmiah Teknik Elektro, 2020)
Inverters widely applied in the industrial world, one of which is in controlling the speed and torque of the induction motor. The main component of an inverter is usually  MOSFET or IGBT. MOSFET has large enough value in the turn-on phase.. The load that has an inductance value, IGBT switching losses will increase. IGBT has losses due to tailing current during fall time. This Final Project research aims design an H-bridge topology inverter using IGBT with SPWM triggering technique based on 16-bit dsPIC30f4011 microcontroller equipped with a bootstrap circuit and aims to regulate motor speed. Inverter testing is done by varying the frequency value, then analyzing efficiency and hamonisa when the inverter is in  no-load and load condition. H-bridge type inverter with bootstrap capacitor without filter and using motor filter has been successfully realized. The average efficiency value of the inverter in the no-load condition is 86.07%, while the load condition is 86.8%. When the inverter no load condition, the average voltage THD value is 6.02%, while the average current THD value is 12.56%, The condition is obtained for an average voltage THD value of 9.48% , while the average THD value of 10.9%.